(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2006)
Five rats were exposed to a procedure in witch the final link on a chain of two responses was followed by water only if the first link responses were emitted in a presence of a sound. After preliminary training of nose poking and lever pressing responses, five experimental phases were introduced. The response rate of nose poking in the presence and absence of the supposed establishing operation was recorded during the entire procedure. The results showed that for four out of five subjects the sound presentations to functioned as a transitive conditioned establishing operations and, as such, evoked nose poking responses (evocative effect) established the onset of the light presentations as conditioned reinforces to those responses (reinforce-establishing effect).